2020
DOI: 10.3847/1538-4357/ab6dcc
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Long Convergence Times in a 3D GCM Simulation of the Sub-Neptune Gliese 1214b

Abstract: We present gray gas general circulation model (GCM) simulations of the tidally locked mini-Neptune GJ 1214b. On timescales of 1,000-10,000 Earth days, our results are comparable to previous studies of the same planet, in the sense that they all exhibit two off-equatorial eastward jets. Over much longer integration times (50,000-250,000 Earth days) we find a significantly different circulation and observational features. The zonal-mean flow transitions from two off-equatorial jets to a single wide equatorial je… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 62 publications
3
46
0
Order By: Relevance
“…This situation may be the case for WASP-43b but also generally for ultra-hot Jupiters (see Table 1, most tidally locked ultra-hot Jupiter are expected to have rotation periods faster than 1.5 days). The possible importance to resolve deeper layers and a sufficiently long simulation times has been further confirmed by Wang & Wordsworth (2020); Showman et al (2020). Here, we take the opportunity to offer a first discussion on what effect the choice of the inner boundary may have on the cloud coverage of the hot giant gas planets, WASP-43b.…”
Section: The Effect Of the Inner Boundary On Gcm Results For The Example Of Wasp-43bmentioning
confidence: 81%
“…This situation may be the case for WASP-43b but also generally for ultra-hot Jupiters (see Table 1, most tidally locked ultra-hot Jupiter are expected to have rotation periods faster than 1.5 days). The possible importance to resolve deeper layers and a sufficiently long simulation times has been further confirmed by Wang & Wordsworth (2020); Showman et al (2020). Here, we take the opportunity to offer a first discussion on what effect the choice of the inner boundary may have on the cloud coverage of the hot giant gas planets, WASP-43b.…”
Section: The Effect Of the Inner Boundary On Gcm Results For The Example Of Wasp-43bmentioning
confidence: 81%
“…Following the recommendation of Sainsbury-Martinez et al (2019), we initialized our model with a hot adiabatic temperature profile. This allows for a comparatively fast convergence of the model to a steady state, even for the deep atmospheric layers, which are known to exhibit prohibitively long convergence times (additionally, see the discussions in Mayne et al 2017;Carone et al 2020;Wang & Wordsworth 2020). From there, all models were run for 1500 (Earth) days with time steps of 25 seconds, and the output has been averaged over the final 100 days of the simulation.…”
Section: Dynamical Climatementioning
confidence: 99%
“…Indeed, it has been shown that atmospheric chemistry can be altered by the internal temperature (Agúndez et al 2014b;Fortney et al 2020). On top of that, the convergence of deep atmospheric layers is a well-known problem in GCM simulations (Amundsen et al 2016;Mayne et al 2017;Carone et al 2020;Wang & Wordsworth 2020;Showman et al 2020). As input temperatures for chemical disequilibrium studies are often derived from GCM simulations (e.g.…”
Section: Observing Methanementioning
confidence: 99%
See 1 more Smart Citation
“…Convergence of the whole simulated domain is therefore bottlenecked by the extremely long radiative timescale in the deep layers. Recent GCM experiments by Wang and Wordsworth (2020) showed that several hundred simulated years are needed for the deep flow to converge if assuming an 80-bar bottom boundary pressure. Mendonça (2020) showed that several tens of simulated years are required for the equatorial jet to equilibrate.…”
Section: Deep Boundary Conditions and Integration Timesmentioning
confidence: 99%